Exploring The Playwright’s Perspectives of Teaching Through Proverbs: A Study of Olanma By Tracie Uto-Ezeajugh (Integral Research, 2025)
Proverb is a communication and language device. It is one of the tools a playwright uses to communicate his message to his readers and audience. They actively teach morals, ethical behaviours, and kindness. The way a writer manipulates this language tool determines how his message is accepted. This work is to highlight the importance of proverbs in aiding creative writers and playwrights in their crafts. Olanma by Tracie Utoh-Ezeajugh served as the case study. This work therefore used the content analysis approach of the qualitative research methodology to explore the role of a playwright in teaching through his craft. The choice of methodology is for in dept analysis of the case study. The findings revealed that proverbs aided the playwright to actualize her thoughts and convey her messages to her readers. The data is contextually analyzed, interpreted and objectively evaluated with a view to locating the lessons taught through the usage of proverbs in her work. The study concludes that proverbs with their deep meanings are veritable tools for playwrights to use in their craft for the education of the masses and mastery of their craft. It recommends the teaching of proverbs in our schools to inculcate morals and values as well as assist in the development of critical thinking in our young ones.
Keywords: Playwrights, Teaching, Perspectives, Proverbs, Education.